2023
DOI: 10.1136/bmjdrc-2022-003075
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes with poor-control HbA1c is cardiovascular disease ‘risk equivalent’ for mortality: UK Biobank and Hong Kong population-based cohort study

Abstract: IntroductionType 2 diabetes mellitus (T2DM) has traditionally been considered a coronary heart disease ‘risk equivalent’ for future mortality, but significant heterogeneity exists across people with T2DM. This study aims to determine the risk of all-cause mortality of patients with cardiovascular disease (CVD) and T2DM in UK and Hong Kong, with stratifications for hemoglobin A1 (HbA1c) concentrations, compared with those without CVD and diabetes mellitus.Research design and methodsThis is a retrospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“… 25 , 26 A recent study showed that the excess mortality associated with T2DM was 25–45% higher among patients with controlled T2DM (HbA1c <7%) than in individuals without diabetes and cardiovascular disease, and that the risk was substantially higher (82–151%) in patients with HbA1c ≥9%. 26 Consequently, to reduce the risk for premature mortality, patients with uncontrolled diabetes require intensification of therapy and close monitoring and guidance, including the initiation or intensification of insulin therapy when clinically required to achieve glycemic control. 9 , 27 , 28 …”
Section: Introductionmentioning
confidence: 99%
“… 25 , 26 A recent study showed that the excess mortality associated with T2DM was 25–45% higher among patients with controlled T2DM (HbA1c <7%) than in individuals without diabetes and cardiovascular disease, and that the risk was substantially higher (82–151%) in patients with HbA1c ≥9%. 26 Consequently, to reduce the risk for premature mortality, patients with uncontrolled diabetes require intensification of therapy and close monitoring and guidance, including the initiation or intensification of insulin therapy when clinically required to achieve glycemic control. 9 , 27 , 28 …”
Section: Introductionmentioning
confidence: 99%